2022
DOI: 10.2478/fiqf-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and New Business Entry

Abstract: The issue of the relationship between financial literacy and entrepreneurship is still not a fully explored research area. On the one hand, there are common views that financial literacy and education in finance are necessary in every individual’s life, and that an insufficient level of financial literacy may result in erroneous economic decisions. On the other hand, research on the impact of narrowly defined financial literacy on business start-up decisions is still rare. As a result, there are no clear indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Financial literacy is described as knowledge of financial concepts and skills to manage financial resources. Studies by Aldi et al [39] and Skica et al [40] have shown that students who have financial literacy are more likely to be successful entrepreneurs. On the other hand erroneous financial decisions can impact negatively on an entrepreneurial venture.…”
Section: Financial Literacymentioning
confidence: 99%
“…Financial literacy is described as knowledge of financial concepts and skills to manage financial resources. Studies by Aldi et al [39] and Skica et al [40] have shown that students who have financial literacy are more likely to be successful entrepreneurs. On the other hand erroneous financial decisions can impact negatively on an entrepreneurial venture.…”
Section: Financial Literacymentioning
confidence: 99%
“…The results showed that entrepreneurial financial literacy benefits the sustainability of small businesses. Skica et al (2022) analyzed the relationship between financial knowledge and a new business entry. For this, the authors used data from the Global Entrepreneurship Monitor (GEM), specifically the Adult Population Survey (APS) Global National Level Data.…”
Section: Financial Knowledgementioning
confidence: 99%
“…Financial literacy affects not only a person's quality of life but also sustainable economic development (Swiecka et al, 2020), the development of entrepreneurship (van Rooij et al, 2011;Riepe et al, 2020;Graña-Alvarez et al, 2022), and the improvement of business activity in region or country (Yin et al, 2015;Barba-Sánchez et al, 2018;Skica et al, 2022).…”
Section: Introductionmentioning
confidence: 99%